Preparation of MED1(transcription mediator subunit) gene nanocarrier and its mechanism of action on liver cell regeneration in chronic acute liver failure. Issue 1 (1st January 2021) - Guo, Jinwei; Zhang, Zhixiang; Zhu, Jincan
ABSTRACT: Liver failure has attracted attention in clinical work due to its high mortality, and the development of liver transplantation is restricted by various factors. Therefore, it is very important to carry out research on the mechanism of liver cell regeneration. This article has studied in depth the preparation of MED1 gene nanocarriers, collected human plasmids and cells through experimental materials and experimental instruments, and conducted comparative research on conventional culture. This question conducts a regeneration experiment on liver cells in chronic-onset acute liver failure, divides patients into an experimental group and a control group, and understands the recovery of liver function according to the screening of their plasma samples and separation of plasma. This article selects the commonly used clinical biological markers, such as Na+, AFP, Alb, CHE (serum cholinesterase) and other indicators to reflect the regeneration ability of liver function. The incidence of surgical complications in the control group, such as ascites, infection, bleeding, HE, hepatorenal syndrome, and hyponatremia were 71.3%, 87.4%, 16.1%, 41.4%, 19.5%, and 33.3%, respectively. Significantly higher than the experimental group, the difference was statistically significant (P < 0.05); while gender, age, PLT level and whether to use hormones, artificial liver or not there was no significant difference between the two groups (P > 0.05). Graphical Abstract: uf0001